Wafer‐Scale Synthesis of Mixed‐Dimensional Heterostructures via Manipulating Platinization Conditions - Yi Rang Lim; Seunghun Jang; Garam Bae; Hye Yoon Jeon; Cheolho Jeon; Da Som Song; Yeong Min Kwon; Moonjeong Jang; Soonmin Yim; Sung Myung; Sun Sook Lee; Hyunju Chang; et al. (Advanced Electronic Materials, 2023)
Abstract 2D van der Waals (vdW) hetero integration, which features exotic interplanar interactions derived from mixed‐dimensional heterostructures, is an emergent platform for implementing high‐performance electronics and broadband/wavelength‐tunable photodetectors. However, the production of large‐area 2D spatially homogeneous transition‐metal dichalcogenides (TMDs) and elucidation of the electrostatic dynamics governing the interlayer interactions are two paramount prerequisites for realizing practical 2D‐TMD‐heterostructure‐based photodetectors. Here, a wafer‐scale synthesis of mixed‐dimensional Pt–MoS2‐based vdW heterostructures is unprecedentedly demonstrated by manipulating the platinization conditions. The rationally designed platinization yields dimensionality‐tailored Pt, including Pt nanofilm, Pt nanoparticles, and Pt atoms, with MoS2 as host platform. From density functional theory calculations, this study insights that Mo vacancy sites on the MoS2 surface are thermo‐dynamically favorable sites for Pt with an adsorption energy of −2.25 eV, then Pt clusters are sequentially formed neighboring the specific Pt‐substituted position with a formation energy of 1.30 eV. Intensive microscopic and spectroscopic analyses reveal the structural, chemical, and electrical features, validating the proposed dynamics‐related mechanism. The dimensionality‐tailored vdW heterostructures exhibit outstanding optoelectrical properties with excellent photoresponsivity (2.04 mA W−1) and highly sensitive detectivity (9.82 × 106 cm Hz1/2 W−1).